Virtuous integrative social robotics for ethical governance - Anshu Saxena Arora; Arlene Marshall; Amit Arora; John R. McIntyre (Discover Artificial Intelligence)
Abstract This research conceptualizes virtuous integrative social robotics (VISR) as a value-driven philosophy for developing and designing social robots and robotic applications. It encompasses shared ethical principles highlighted as autonomy, responsibility, and transparency (ART) for social robotics in the VISR context. Virtue ethics is explored as a means for programming social robots as artificial moral agents, placing human values as the basis of robot design. It is based on the ‘non-replacement principle’ whereby social robots should behave as a virtuous human would. Finally, this research provides managerial implications and promises to find innovative ways based on ethical decision-making and improving ethical transparency for human–robot interaction (HRI), unification, trust, and collaboration more than ever before.